Interleukin-33 deficiency exacerbated experimental autoimmune encephalomyelitis with an influence on immune cells and glia cells. (September 2018) - Xiao, Yifan; Lai, Lin; Chen, Huoying; Shi, Junyu; Zeng, FanFan; Li, Jun; Feng, Huiting; Mao, Jie; Zhang, Feng; Wu, Naming; Xu, Yong; Tan, Zheng; et al.
Highlights: IL-33 knockout aggravates the development of EAE. IL-33 knockout inhibits Th2, NK cells and promotes Th1/Th17 cells. IL-33 knockout promotes iNOS-producing microglia/macrophages and CD11C + CD11B + DCs. IL-33 suppresses the activation of astrocytes and the release of MCP-1/CCL2, TNF-α from them. IL-33 suppresses TNF-α releasing from primary microglia. Abstract: Interleukin (IL)-33, a member of the IL-1 cytokine family, is highly expressed in central nervous system (CNS), suggesting its potential role in CNS. Although some studies have focused on the role of IL-33 in multiple sclerosis (MS) / experimental autoimmune encephalomyelitis (EAE), an autoimmune disease characterized by demyelination and axonal damage in CNS, the exact role of IL-33 in MS/EAE remains unclear and controversial. Here, we used IL-33 knockout mice to clarify the role of endogenous IL-33 in EAE by simultaneously eliminating its role as a nuclear transcription factor and an extracellular cytokine. We found that the clinical score in IL-33 knockout EAE mice was higher accompanied by more severe demyelination compared with the wild-type (WT) EAE mice. As for the main immune cells participating in EAE in IL-33 knockout mice, pathogenic effector T cells increased both in peripheral immune organs and CNS, while CD4 + FOXP3 + regulatory T cells decreased in spleen and lymph nodes, Th2 cells and natural killer (NK) cells decreased in CNS. Additionally, the populations of microglia/macrophages and CD11C + CD11B + dendritic cells (DCs) increased in CNS of IL-33 knockout mice with EAE, among which iNOS-producing microglia/macrophages increased. Moreover, resident astrocytes/microglia were more activated in IL-33 knockout mice with EAE. In vitro, after blocking the IL-33, the proliferation of primary astrocytes, the production of MCP-1/CCL2 and TNF-α by astrocytes, and the production of TNF-α by primary microglia stimulated by the homogenate of the peak stage of EAE were increased. Our results indicate that IL-33 plays a protective role in EAE and exerts extensive influences on multiple immune cells and neural cells involved in EAE.